Protection of Human Rights in Reclamation in Coastal Areas and Small Islands - Syaiful Hadi; Tahegga Primananda Alfath; Trianita Yandhini Syarifudin (Lex Scientia Law Review, 2018)
Reclamation of coastal areas is becoming increasingly widespread in various regions, under the pretext of increasing investment and regional income, permits to carry out reclamation seem easy, BUMN/BUMD or the private sector are made partners of cooperation by the government as executors of reclamation projects. The reclamation project legalized by the government is based on the existence of marine conservation, investment in coastal areas and small islands, and the construction of seaside dwellings. Even though the reclamation project is in direct contact with the lives of the surrounding community, especially fishing communities in coastal areas and small islands. Privatization and commodification of marine resources which then displaces the existence of coastal communities and eliminates their access to their livelihoods, this is a violation of human rights. Based on this, the legal issues that will be discussed in this study are first, the government's obligation to protect human rights for communities in coastal areas and small islands. Second, whether Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands and the regulations under it have provided access to protection of the human rights of coastal communities and small islands.